Manufacturing process of aluminum wafer adsorption disc of wafer detection equipment

CN122956191APending Publication Date: 2026-10-23JIN KANG BAN DAO TI KE JI (SHANG HAI) YOU XIAN GONG SI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611080701.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]然而该方法存在以下不足:硬质阳极氧化过程中膜层生长产生的体积膨胀效应使膜层内部形成残余压应力,二次研磨仅从几何维度上去除余量,未从微观结构层面释放膜层残余应力,吸盘在后续热循环服役中残余应力松弛导致基体-膜层界面发生微滑移,平面度衰减速率快,经500次25℃至80℃热循环后平面度从5μm衰减至12μm以上;气槽和气道在硬质氧化前已加工完成,氧化过程中电解液渗入气槽和导孔内部并在孔壁形成氧化膜,孔内氧化膜厚度不均且难以彻底清洗,残留电解液在后续服役中缓慢释出腐蚀性离子,污染检测环境并加速孔壁局部腐蚀,导致真空泄漏率随服役时间递增;硬质氧化膜的多孔层未进行针对性密封处理,膜层微孔在真空吸附工况下成为泄漏通道,吸盘真空泄漏率偏高,需配置更大功率的真空泵才能维持吸附力,且微孔中易滞留颗粒物造成晶圆背面污染

Benefits of technology

1、本发明通过在硬质阳极氧化后增设阶梯式真空时效处理,在150℃-170℃保温阶段使氧化膜微观结构发生弛豫与重组,释放膜层生长过程中产生的残余压应力,实现膜层应力自平衡;当时效温度低于150℃时膜层微观结构弛豫驱动力不足,残余应力释放不充分,经500次热循环后平面度衰减至10μm以上;当时效温度高于170℃时膜层微观结构过度重组导致脱水收缩不均匀,膜层与基体界面产生微裂纹,平面度反而急剧劣化至15μm以上,同时膜层硬度下降约18%;仅在150℃-170℃的临界窗口内,膜层微观结构弛豫程度与膜层结构完整性精确匹配,残余应力近乎完全释放,经500次热循环后平面度衰减量不超过2μm,面型稳定性较现有技术提升4倍以上;190℃-210℃保温阶段进一步消除基体-膜层界面的残余剪切应力,防止界面微滑移。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of precision component machining of semiconductor manufacturing equipment, in particular to a manufacturing process of an aluminum wafer adsorption disc of a wafer detection equipment, which comprises blank cutting, stress relief tempering, CNC precision machining, air groove air channel shielding treatment, hard anodic oxidation, shielding layer removal and hole cleaning, step vacuum aging, fluorine-containing silane vacuum impregnation hole sealing, thermal curing, precision grinding and ultrasonic cleaning detection. A polyvinyl alcohol aqueous solution with a polymerization degree of 1700-2000 and an alcoholysis degree of 87%-90% is used to coat a shielding layer, hard anodic oxidation is carried out under a sulfuric acid-oxalic acid composite electrolyte and a step current, step vacuum aging at a critical window of 150 DEG C-170 DEG C makes the microstructure of the oxidation film relax and recombine to release residual compressive stress and realize stress self-balancing, fluorine-containing silane vacuum impregnation-thermal curing realizes deep sealing of micropores, the retained thickness of the oxidation film after grinding is not less than 30 mu m, the flatness attenuation after 500 times of thermal cycling is not more than 2 mu m, and the vacuum leakage rate is not more than 1*10 ‑8 Pa.m 3 / s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of precision component processing technology for semiconductor manufacturing equipment, and specifically to a manufacturing process for an aluminum wafer adsorption disk for a wafer inspection device. Background Technology

[0002] Wafer inspection equipment is a core component of the semiconductor manufacturing industry chain, used for high-precision inspection of wafer surface defects, film thickness, and electrical parameters. During inspection, the wafer must be stably adsorbed and fixed on an adsorption plate. The surface accuracy and vacuum sealing of the adsorption plate directly determine the wafer's positioning accuracy and the reliability of the inspection results. Aluminum alloys are the mainstream substrate for adsorption plates in wafer inspection equipment due to their advantages such as good thermal conductivity, high specific strength, excellent processing performance, and low cost.

[0003] CN116252111A discloses a precision machining method for semiconductor wafer chucks. The method adopts a process route of tempering to eliminate internal stress in the material, CNC machining of air grooves and air channels, rough grinding of thickness, first fine grinding, natural hard oxidation and second fine grinding. After forming a hard oxide film on the aluminum alloy surface, the flatness is controlled by second grinding.

[0004] However, this method has the following shortcomings: the volume expansion effect generated during film growth in the hard anodizing process creates residual compressive stress inside the film; secondary grinding only removes excess material geometrically and does not release residual stress at the microstructural level; the residual stress relaxation of the suction cup during subsequent thermal cycling leads to micro-slippage at the substrate-film interface, resulting in a rapid flatness decay rate, with flatness decreasing from 5μm to over 12μm after 500 thermal cycles from 25℃ to 80℃; the air grooves and air channels are already processed before hard anodizing, and the electrical components are affected during the anodizing process. The electrolyte seeps into the gas groove and guide hole and forms an oxide film on the hole wall. The oxide film thickness inside the hole is uneven and difficult to clean thoroughly. The residual electrolyte slowly releases corrosive ions during subsequent service, contaminating the detection environment and accelerating local corrosion of the hole wall, resulting in an increase in vacuum leakage rate over service time. The porous layer of the hard oxide film is not specifically sealed, and the micropores of the film layer become leakage channels under vacuum adsorption conditions, resulting in a high vacuum leakage rate of the suction cup. A higher power vacuum pump is required to maintain the adsorption force, and particles are easily trapped in the micropores, causing contamination on the back side of the wafer.

[0005] CN119121347A discloses a method for preparing anodized coatings for semiconductor manufacturing equipment components. This method involves eliminating second-phase clusters on the surface of an aluminum alloy using vacuum laser treatment followed by anodizing and sealing. However, this method is designed for corrosion protection of non-precision bearing surfaces such as chamber liners. Its technical solution does not cover micron-level flatness control, oxidation protection of gas channels and ducts, or synergistic optimization of vacuum sealing performance. Therefore, the process route cannot be directly applied to the precision manufacturing of wafer adsorption pads.

[0006] A comprehensive analysis of existing technologies reveals the following shortcomings in the manufacturing of aluminum wafer adsorption pads: residual stress in the hard anodized film layer is not effectively released, and flatness decay exceeds the requirements for detection accuracy after thermal cycling; unintended oxide films formed on the walls of the gas grooves and gas channels during oxidation lead to leakage channels and corrosion risks; the porous oxide film layer is not sealed for vacuum adsorption conditions, resulting in a high leakage rate and easy retention of particulate matter; these three problems are coupled together, with residual stress causing the expansion of microcracks in the film layer, leading to the failure of the porous layer seal, and the unintended oxide film peeling off the pore walls, forming particulate matter that further contaminates the back side of the wafer, creating a vicious cycle. Summary of the Invention

[0007] The primary objective of this invention is to provide a manufacturing process for an aluminum wafer adsorption plate for a wafer inspection device.

[0008] A further objective of this invention is to provide a manufacturing process for an aluminum wafer adsorption pad in a wafer inspection device, comprising the following steps: Step 1: Select 6061-T6 aluminum alloy sheet and cut it into a circular blank; Step 2: Place the round blank in a vacuum heat treatment furnace, heat it to 250℃-270℃ at a rate of 2℃ / min-4℃ / min, hold it at that temperature for 8h-12h, and then cool it to room temperature at a rate of 1℃ / min-2℃ / min. Step 3: Perform CNC precision machining on the tempered blank, mill the outer circle to the designed diameter D, and machine the thickness to the designed thickness H minus 0.02mm-0.05mm. Mill air grooves on the front of the disc, and drill air channels vertically from the outer circumference of the disc to the center. Drill at least one non-penetrating guide hole vertically on the disc at each air groove position to make the guide hole connect with the air channel. Drill pin holes and positioning pin holes. Step 4: Coat the inner wall surfaces of the air groove, air passage, guide hole and pin hole with a soluble polyvinyl alcohol shielding layer. The soluble polyvinyl alcohol has a degree of polymerization of 1700-2000 and a degree of alcoholysis of 87%-90%. Coat with a polyvinyl alcohol aqueous solution with a mass concentration of 10%-15%. The shielding layer thickness is 0.1mm-0.3mm. After coating, dry at 60℃-80℃ for 1h-2h to cure the shielding layer. Step 5: The shielded billet is placed in a sulfuric acid-oxalic acid composite electrolyte for hard anodizing. The electrolyte temperature is -2℃ to 2℃, the sulfuric acid concentration is 180g / L-220g / L, the oxalic acid concentration is 8g / L-12g / L, and the initial current density is 0.8A / dm³. 2 -1.2A / dm 2 After oxidation for 15-20 minutes, the current density was gradually increased to 2.5 A / dm³. 2 -3.0A / dm 2The total oxidation time is 90-120 minutes, forming a hard anodized film with a thickness of 40-60 μm on the surface of the blank. Step 6: Immerse the hard anodized blank in 50℃-60℃ deionized water for 20min-30min to dissolve and remove the shielding layer, and then rinse the air groove, air channel, guide hole and ejector pin hole inner wall with high pressure deionized water. Step 7: Place the cleaned billet in a vacuum heat treatment furnace, with a vacuum degree not exceeding 1×10⁻⁶. -2 Under Pa conditions, the temperature is increased to 150℃-170℃ at 1℃ / min-2℃ / min and held for 3h-5h, then increased to 190℃-210℃ at 0.5℃ / min-1℃ / min and held for 1h-2h, and then cooled to room temperature in the furnace. Step 8: Immerse the billet in a 2%-4% (w / w) 1H,1H,2H,2H-perfluorooctyltriethoxysilane ethanol solution, evacuate to 50Pa-200Pa and hold for 15-25 minutes, then slowly depressurize to atmospheric pressure and maintain for 10-15 minutes. Step 9: Heat the temperature to 120℃-140℃ at a rate of 2℃ / min-3℃ / min and hold for 1-2 hours for heat curing. Step 10: Precision grind the adsorption surface of the billet to the designed thickness H with a single feed rate of 1μm-3μm. After grinding, the oxide film on the adsorption surface should retain a thickness of not less than 30μm. Step 11: Ultrasonic cleaning, testing, and clean packaging.

[0009] Preferably, the thickness of the 6061-T6 aluminum alloy sheet in step one is not less than H plus 5mm, and the diameter is not less than D plus 10mm.

[0010] Preferably, the pressure of the high-pressure deionized water in step six is ​​0.5MPa-0.8MPa.

[0011] Preferably, in step seven, the holding time for heating to 150℃-170℃ at a rate of 1℃ / min-2℃ / min is 4 hours.

[0012] Preferably, in step eight, the vacuum is evacuated to 100 Pa and held for 20 minutes, then slowly depressurized to atmospheric pressure and held for 12 minutes.

[0013] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention employs a stepped vacuum aging treatment after hard anodizing. During the 150℃-170℃ holding stage, the microstructure of the oxide film relaxes and reorganizes, releasing the residual compressive stress generated during film growth and achieving stress self-balancing. When the aging temperature is below 150℃, the driving force for relaxation of the film's microstructure is insufficient, and the residual stress is not fully released, resulting in a flatness decay to over 10μm after 500 thermal cycles. When the aging temperature is above 170℃, excessive microstructure reorganization leads to uneven dehydration and shrinkage. Microcracks appear at the interface between the film and the substrate, and the flatness deteriorates sharply to more than 15 μm, while the hardness of the film decreases by about 18%. Only within the critical window of 150℃-170℃, the relaxation degree of the film microstructure is precisely matched with the integrity of the film structure, and the residual stress is almost completely released. After 500 thermal cycles, the flatness attenuation is no more than 2 μm, and the surface stability is more than 4 times better than the existing technology. The heat preservation stage of 190℃-210℃ further eliminates the residual shear stress at the substrate-film interface and prevents the interface microslippage.

[0014] 2. This invention coats the inner walls of the gas groove, gas channel, guide hole, and ejector pin hole with a soluble polyvinyl alcohol shielding layer before hard anodizing. During the anodizing process, the shielding layer prevents the electrolyte from contacting the aluminum substrate of the hole wall, thus preventing the formation of an oxide film on the hole wall. After anodizing, the shielding layer is dissolved by soaking in warm water and rinsed with high-pressure deionized water, restoring the hole wall to the bare aluminum alloy substrate with a smooth surface free of oxide film. This fundamentally eliminates leakage channels caused by uneven oxide film thickness inside the hole and corrosion risks caused by residual electrolyte. Compared with the method of removing the oxide film inside the hole with a milling cutter after anodizing, this invention avoids secondary damage to the hole wall and metal debris residue caused by milling, reducing the vacuum leakage rate to 5×10⁻⁶. -8 Pa·m 3 / s or less.

[0015] 3. This invention employs a combined vacuum impregnation-thermosetting sealing process using fluorinated silanes. Vacuum impregnation allows the fluorinated silane solution to deeply penetrate the nanoscale micropores of the oxide film under pressure differential. Thermosetting causes the fluorinated silane to undergo a condensation reaction on the inner wall of the micropores, forming a dense fluorosiloxane cross-linked network. This achieves deep sealing of the micropores rather than surface plugging. The fluorosiloxane cross-linked network has extremely low surface free energy, possesses both hydrophobic and oleophobic properties and chemical corrosion resistance, effectively blocking gas leakage channels through the micropores under vacuum adsorption conditions. Simultaneously, it inhibits the adhesion and retention of particulate matter within the micropores, reducing the vacuum leakage rate of the adsorption disk to 1×10⁻⁶. -8 Pa·m 3 With a density of less than 1 / s, the particle contamination count on the back side of the wafer is reduced to less than 5 per wafer; compared with traditional hot water sealing or nickel salt sealing, the filling rate of fluorinated silane sealing in the depth direction of micropores is increased from about 60% to more than 90%, and the sealing layer does not crack or fall off under thermal cycling conditions.

[0016] 4. This invention integrates three aspects: self-balancing of film stress, oxide shielding protection of pore walls, and deep sealing with fluorinated silane. Self-balancing of film stress ensures that the oxide film does not generate microcracks during thermal cycling, and the elimination of microcracks prevents the sealing layer from peeling off and failing at the cracks. Oxidation shielding protection of pore walls ensures that the inner wall of the gas groove and gas channel is smooth and leak-free, reducing the overall leakage load of the vacuum system. Deep sealing with fluorinated silane achieves a durable seal on the intact film without microcracks. The three aspects form a positive feedback loop: the integrity of the film ensures the durability of the sealing, the durability of the sealing ensures vacuum stability, and vacuum stability reduces thermal stress fluctuations.

[0017] 5. The aluminum wafer adsorption disk prepared by this invention has an adsorption surface flatness of no more than 3 μm, and after 500 thermal cycles from 25°C to 80°C, the flatness decreases by no more than 2 μm, and the vacuum leakage rate is no more than 1 × 10⁻⁶. -8 Pa·m 3 / s, with a surface roughness Ra of no more than 0.4μm, and its overall performance is significantly better than that of existing aluminum wafer adsorption disks. Detailed Implementation

[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example

[0019] raw material: 6061-T6 aluminum alloy sheet, 20mm thick, 190mm in diameter, sourced from Northeast Light Alloy Co., Ltd., chemical composition conforms to GB / T 3190-2020 standard, T6 tensile strength 310MPa.

[0020] Preparation process: Step 1, Blank preparation: Cut the 6061-T6 aluminum alloy sheet into a circular blank with a diameter of 190mm and a thickness of 20mm. The design of the adsorption plate diameter D is 180mm and the design of the thickness H is 12mm.

[0021] Step 2, stress-relieving tempering: Place the round blank in a vacuum heat treatment furnace, heat it to 260℃ at a rate of 3℃ / min, hold it at that temperature for 10 hours, and cool it to room temperature at a rate of 1.5℃ / min.

[0022] Step 3, CNC precision machining: Perform CNC precision machining on the tempered blank, mill the outer circle to a diameter of 180mm, and machine the thickness to 11.97mm. Mill the air groove to a depth of 0.6mm on the front of the disk. Drill the air passage with a diameter of 3mm vertically from the outer circumference of the disk to the center. Drill a non-penetrating guide hole with a diameter of 1mm vertically on the disk at each air groove position to connect the guide hole with the air passage. Drill 3 ejector pin holes with a diameter of 4mm and 2 locating pin holes with a diameter of 6mm.

[0023] Step 4, shielding treatment of air grooves and air passages: Prepare a 12% (w / w) polyvinyl alcohol solution with a degree of polymerization of 1700-2000 and a degree of hydrolysis of 87%-90%. Use a brush to evenly coat the solution onto the inner wall of the air groove, air passage, guide hole and pin hole. The shielding layer thickness is about 0.2 mm. After coating, dry at 70℃ for 1.5 h to cure the shielding layer.

[0024] Step 5, Hard Anodizing: The shielded billet is placed in a sulfuric acid-oxalic acid composite electrolyte for hard anodizing. The electrolyte temperature is 0℃, the sulfuric acid concentration is 200g / L, the oxalic acid concentration is 10g / L, and the initial current density is 1.0A / dm³. 2 After oxidation for 18 minutes, the current density was gradually increased to 2.8 A / dm³. 2 The total oxidation time was 105 min, forming a hard anodized film with a thickness of about 50 μm on the surface of the blank.

[0025] Step 6, Shielding layer removal and channel cleaning: Immerse the hard anodized blank in 55℃ deionized water for 25 minutes to dissolve and remove the polyvinyl alcohol shielding layer. Then, use high-pressure deionized water at 0.6MPa to rinse the air groove, air channel, guide hole and ejector pin hole inner wall in sequence, rinsing each three times for 2 minutes each time.

[0026] Step 7, Stepped Vacuum Aging: Place the cleaned billet in a vacuum heat treatment furnace, and aging it at a vacuum degree of 5×10⁻⁶. - 3 Under Pa conditions, the temperature was increased to 160℃ at a rate of 1.5℃ / min and held for 4 hours. Then, the temperature was increased to 200℃ at a rate of 0.8℃ / min and held for 1.5 hours. The furnace was then cooled to room temperature.

[0027] Step 8, Vacuum impregnation and sealing with fluorinated silane: Prepare a 3% (w / w) fluorinated silane ethanol solution of 1H,1H,2H,2H-perfluorooctyltriethoxysilane. Immerse the vacuum-aged billet in the solution, place it in a vacuum impregnation device, evacuate to 100 Pa, maintain the pressure for 20 min, slowly depressurize to atmospheric pressure and maintain for 12 min.

[0028] Step 9, heat curing: Place the impregnated blank in a drying oven and heat it to 130℃ at a rate of 2.5℃ / min, and keep it at that temperature for 1.5h.

[0029] Step 10, Precision Grinding: The adsorption surface of the billet is precision ground with a single feed rate of 2μm. During the grinding process, the flatness is checked once with a laser interferometer every 5μm of thickness. Grind to the designed thickness of 12.00mm. After grinding, the oxide film on the adsorption surface retains a thickness of about 40μm.

[0030] Step 11, Ultrasonic Cleaning and Testing: Place the ground adsorption plate in ultrapure water for ultrasonic cleaning at a frequency of 50 kHz for 20 minutes. Then dry it with high-purity nitrogen gas with a purity of 99.999% and vacuum seal it in a Class 100 clean environment. Example

[0031] raw material: 6061-T6 aluminum alloy sheet, 22mm thick, 310mm in diameter, sourced from Northeast Light Alloy Co., Ltd., chemical composition conforms to GB / T 3190-2020 standard, T6 tensile strength 310MPa.

[0032] Preparation process: Step 1, Blank preparation: Cut 6061-T6 aluminum alloy sheet into circular blanks with a diameter of 310mm and a thickness of 22mm. Design the adsorption plate diameter D to be 300mm and the design thickness H to be 14mm.

[0033] Step 2, stress-relieving tempering: Place the round blank in a vacuum heat treatment furnace, heat it to 270°C at a rate of 2°C / min, hold it at that temperature for 12 hours, and then cool it to room temperature at a rate of 1°C / min.

[0034] Step 3, CNC precision machining: Perform CNC precision machining on the tempered blank, mill the outer circle to a diameter of 300mm, and machine the thickness to 13.96mm. Mill the air groove to a depth of 0.8mm on the front of the disk. Drill the air passage vertically from the outer circumference of the disk to the center with a diameter of 4mm. Drill a non-penetrating guide hole with a diameter of 1.2mm vertically on the disk at each air groove position to connect the guide hole with the air passage. Drill 4 ejector pin holes with a diameter of 5mm and 3 locating pin holes with a diameter of 8mm.

[0035] Step 4, shielding treatment of air tanks and air passages: Prepare a 15% (w / w) polyvinyl alcohol aqueous solution with a degree of polymerization of 1700-2000 and a degree of hydrolysis of 87%-90%. Inject the solution into the inner wall of the air tank, air passage, guide hole and pin hole using a syringe. The shielding layer thickness is about 0.3 mm. After coating, dry at 80°C for 1 hour to cure the shielding layer.

[0036] Step 5, Hard Anodizing: The shielded billet is placed in a sulfuric acid-oxalic acid composite electrolyte for hard anodizing. The electrolyte temperature is -2℃, the sulfuric acid concentration is 220 g / L, the oxalic acid concentration is 12 g / L, and the initial current density is 0.8 A / dm³. 2 After oxidation for 20 minutes, the current density was gradually increased to 3.0 A / dm³. 2 The total oxidation time is 120 minutes, forming a hard anodized film with a thickness of about 60 μm on the surface of the blank.

[0037] Step 6, Shielding layer removal and channel cleaning: Immerse the hard anodized blank in 60℃ deionized water for 20 minutes to dissolve and remove the polyvinyl alcohol shielding layer. Then, use high-pressure deionized water at 0.8MPa to rinse the air groove, air channel, guide hole and ejector pin hole inner wall in sequence, rinsing each 4 times for 2 minutes each time.

[0038] Step 7, Stepped Vacuum Aging: Place the cleaned billet in a vacuum heat treatment furnace, and aging it at a vacuum degree of 8×10⁻⁶. - 3 Under Pa conditions, the temperature was increased to 170℃ at a rate of 1℃ / min and held for 3 hours. Then, the temperature was increased to 210℃ at a rate of 0.5℃ / min and held for 1 hour. The furnace was then cooled to room temperature.

[0039] Step 8, Vacuum impregnation and sealing with fluorinated silane: Prepare a 4% (w / w) fluorinated silane ethanol solution of 1H,1H,2H,2H-perfluorooctyltriethoxysilane. Immerse the vacuum-aged billet in the solution and place it in a vacuum impregnation device. Evacuate the pressure to 50 Pa, maintain the pressure for 25 min, slowly depressurize to atmospheric pressure and maintain for 15 min.

[0040] Step 9, heat curing: Place the impregnated blank in a drying oven and heat it to 140°C at a rate of 3°C / min, and keep it at that temperature for 1 hour.

[0041] Step 10, Precision Grinding: The adsorption surface of the billet is precision ground with a single feed rate of 1μm. During the grinding process, the flatness is checked once with a laser interferometer every 3μm of thickness. Grind to the designed thickness of 14.00mm. After grinding, the oxide film on the adsorption surface retains a thickness of about 45μm.

[0042] Step 11, Ultrasonic cleaning and testing: Same as in Example 1. Example

[0043] raw material: 6061-T6 aluminum alloy sheet, 18mm thick, 165mm in diameter, sourced from Northeast Light Alloy Co., Ltd., chemical composition conforms to GB / T 3190-2020 standard, T6 tensile strength 310MPa.

[0044] Preparation process: Step 1, Blank preparation: Cut the 6061-T6 aluminum alloy sheet into a circular blank with a diameter of 165mm and a thickness of 18mm. The design of the adsorption plate diameter D is 150mm and the design of the thickness H is 10mm.

[0045] Step 2, stress-relieving tempering: Place the round blank in a vacuum heat treatment furnace, heat it to 250°C at a rate of 4°C / min, hold it at that temperature for 8 hours, and then cool it to room temperature at a rate of 2°C / min.

[0046] Step 3, CNC precision machining: Perform CNC precision machining on the tempered blank, mill the outer circle to a diameter of 150mm, and machine the thickness to 9.98mm. Mill the air groove to a depth of 0.5mm on the front of the disc. Drill the air passage vertically from the outer circumference of the disc to the center with a diameter of 2.5mm. Drill a non-penetrating guide hole with a diameter of 0.8mm vertically on the disc at each air groove position to connect the guide hole with the air passage. Drill 3 ejector pin holes with a diameter of 3mm and 2 locating pin holes with a diameter of 5mm.

[0047] Step 4, shielding treatment of air grooves and air passages: Prepare a 10% (w / w) polyvinyl alcohol solution with a degree of polymerization of 1700-2000 and a degree of hydrolysis of 87%-90%. Use a brush to evenly coat the solution onto the inner wall of the air groove, air passage, guide hole and pin hole. The shielding layer thickness is about 0.1 mm. After coating, dry at 60℃ for 2 hours to cure the shielding layer.

[0048] Step 5, Hard Anodizing: The shielded billet is placed in a sulfuric acid-oxalic acid composite electrolyte for hard anodizing. The electrolyte temperature is 2℃, the sulfuric acid concentration is 180g / L, the oxalic acid concentration is 8g / L, and the initial current density is 1.2A / dm³. 2 After oxidation for 15 minutes, the current density was gradually increased to 2.5 A / dm³. 2 The total oxidation time is 90 minutes, forming a hard anodized film with a thickness of about 40 μm on the surface of the blank.

[0049] Step 6, Shielding layer removal and channel cleaning: Immerse the hard anodized blank in 50℃ deionized water for 30 minutes to dissolve and remove the polyvinyl alcohol shielding layer. Then, use high-pressure deionized water at 0.5MPa to rinse the air groove, air channel, guide hole and ejector pin hole inner wall in sequence, rinsing each three times for 3 minutes each time.

[0050] Step 7, Stepped Vacuum Aging: Place the cleaned billet in a vacuum heat treatment furnace, and aging it at a vacuum degree of 1×10⁻⁶. - 2 Under Pa conditions, the temperature was increased to 150℃ at a rate of 2℃ / min and held for 5 hours, then increased to 190℃ at a rate of 1℃ / min and held for 2 hours, and then cooled to room temperature in the furnace.

[0051] Step 8, Vacuum impregnation and sealing with fluorinated silane: Prepare a 2% (w / w) fluorinated silane ethanol solution of 1H,1H,2H,2H-perfluorooctyltriethoxysilane. Immerse the vacuum-aged billet in the solution, place it in a vacuum impregnation device, evacuate to 200 Pa, maintain the pressure for 15 min, slowly depressurize to atmospheric pressure and maintain for 10 min.

[0052] Step 9, heat curing: Place the impregnated blank in a drying oven and heat it to 120°C at a rate of 2°C / min, and keep it at that temperature for 2 hours.

[0053] Step 10, Precision Grinding: The adsorption surface of the billet is precision ground with a single feed rate of 3μm. During the grinding process, the flatness is checked once with a laser interferometer every 8μm of thickness. Grind to the designed thickness of 10.00mm. After grinding, the oxide film on the adsorption surface retains a thickness of about 35μm.

[0054] Step 11, Ultrasonic cleaning and testing: Same as in Example 1.

[0055] Comparative Example 1 raw material: Same as Example 1.

[0056] Preparation process: The process route disclosed in CN116252111A is as follows: billet cutting - tempering at 260℃ for 10 hours - CNC machining of air grooves and passages - rough grinding to a thickness of 12.35mm - first fine grinding to 12.00mm - natural hard anodizing to 90μm-100μm - second fine grinding to 12.00mm. No shielding treatment, stepped vacuum aging, or fluorinated silane vacuum impregnation sealing is performed.

[0057] Comparative Example 2: raw material: Same as Example 1.

[0058] Preparation process: Similar to Example 1, the only difference is that the stepped vacuum aging in step seven is not performed, and the fluorinated silane vacuum impregnation sealing is performed directly after hard anodizing.

[0059] Comparative Example 3: raw material: Same as Example 1.

[0060] Preparation process: Similar to Example 1, the only difference is that the first stage temperature of the stepped vacuum aging in step seven is 120°C, which is lower than the critical range of 150°C-170°C of this invention. After holding at this temperature for 4 hours, the temperature is raised to 200°C and held for 1.5 hours.

[0061] Comparative Example 4: raw material: Same as Example 1.

[0062] Preparation process: Similar to Example 1, the only difference is that the first stage temperature of the stepped vacuum aging in step seven is 200°C, which is higher than the critical range of 150°C-170°C of this invention. After holding at this temperature for 4 hours, the temperature is raised to 200°C and held for 1.5 hours.

[0063] Comparative Example 5: raw material: Same as Example 1.

[0064] Preparation process: Similar to Example 1, the only difference is that the gas channel shielding treatment in step four is not performed, and the oxide film inside the hole is not treated after oxidation (the unintended oxide film is retained on the hole wall). The remaining steps are the same as in Example 1.

[0065] Comparative Example 6: raw material: Same as Example 1.

[0066] Preparation process: Similar to Example 1, the only difference is that the air channel shielding treatment in step four is not performed. After oxidation, the oxide film inside the hole is removed by a milling cutter. The remaining steps are the same as in Example 1.

[0067] Comparative Example 7: raw material: Same as Example 1.

[0068] Preparation process: Similar to Example 1, the only difference is that in steps eight and nine, traditional hot water sealing is used instead of vacuum impregnation-thermal curing sealing with fluorinated silane: the blank after vacuum aging is immersed in 96°C deionized water for 30 minutes for hot water sealing, without vacuum impregnation and thermal curing with fluorinated silane.

[0069] Comparative Example 8: raw material: Same as Example 1.

[0070] Preparation process: Similar to Example 1, the only difference is that in step seven, an atmospheric pressure air furnace is used instead of a vacuum furnace for aging treatment. The aging temperature and holding time are the same as in Example 1, and the remaining steps are the same as in Example 1.

[0071] Performance testing methods: Flatness inspection: A laser interferometer was used, and the procedure was performed in accordance with GB / T 11337-2004. The height deviation of nine equally spaced points along the diameter direction was measured, and the difference between the maximum and minimum deviations was taken as the flatness value. Each sample was measured three times and the average value was taken.

[0072] Flatness decay test after thermal cycling: The adsorption plate is placed in a high and low temperature test chamber and heated from 25℃ to 80℃ at a rate of 5℃ / min, held for 5 min, and then cooled to 25℃ at a rate of 5℃ / min, held for 5 min, which is one thermal cycle; after a total of 500 thermal cycles, it is taken out and left to stand for 2 h in an environment of 23℃-25℃ before the flatness is measured. The flatness decay is the flatness after thermal cycling minus the flatness before thermal cycling.

[0073] Vacuum leak rate detection: A helium mass spectrometer leak detector was used, performed according to GB / T 15823-2009. The adsorption plate was sealed on the leak detection fixture with the adsorption surface facing upwards. The gas channel of the gas chamber was evacuated to below 10 Pa. Helium was used as the tracer gas and sprayed from above the adsorption surface. The sensitivity of the leak detector was not less than 1×10⁻⁶. -9 Pa·m 3 / s, each sample was measured 3 times and the average value was taken.

[0074] Surface roughness testing: A contact surface roughness tester was used, and the test was performed in accordance with GB / T 3505-2009. The sampling length was 0.8 mm and the evaluation length was 4 mm. The Ra value was measured at 5 equally spaced positions on the adsorption surface and the average value was taken.

[0075] Oxide film hardness testing: A Vickers microhardness tester was used with a load of 0.49 N and a holding time of 15 s. Five points were measured on the cross-section of the oxide film and the average value was taken.

[0076] On the back side of the wafer, particulate matter detection: Place a 300mm silicon wafer on an adsorption plate and vacuum adsorb for 30 minutes, then remove it. Perform the procedure according to SEMI E14-0307. Use a dark field laser scattering particle detector to detect the number of newly added particles on the back side of the wafer. The particle size threshold is not less than 0.16μm.

[0077] Example 1 2.1 3.5 1.4 485 Example 2 2.5 4.2 1.7 490 Example 3 1.8 3.2 1.4 475 Comparative Example 1 5.2 12.8 7.6 460 Comparative Example 2 2.3 11.5 9.2 478 Comparative Example 3 2.8 10.6 7.8 470 Comparative Example 4 4.5 15.2 10.7 398 Comparative Example 5 2.4 3.9 1.5 482 Comparative Example 6 2.2 3.8 1.6 480 Comparative Example 7 2.0 4.8 2.8 482 Comparative Example 8 2.4 9.8 7.4 455 Example 1 <![CDATA[8.2×10 -9 ]]> 3 0.32 Example 2 <![CDATA[9.5×10 -9 ]]> 4 0.35 Example 3 <![CDATA[6.8×10 -9 ]]> 2 0.28 Comparative Example 1 <![CDATA[5.6×10 -7 ]]> 38 0.55 Comparative Example 2 <![CDATA[4.8×10 -7 ]]> 25 0.38 Comparative Example 3 <![CDATA[3.2×10 -7 ]]> 18 0.36 Comparative Example 4 <![CDATA[7.5×10 -7 ]]> 42 0.62 Comparative Example 5 <![CDATA[1.8×10 -7 ]]> 15 0.34 Comparative Example 6 <![CDATA[2.3×10 -7 ]]> 22 0.34 Comparative Example 7 <![CDATA[8.5×10 -8 ]]> 8 0.33 Comparative Example 8 <![CDATA[4.1×10 -7 ]]> 20 0.37 Results analysis: Before thermal cycling, the flatness of Examples 1 to 3 was 1.8 μm to 2.5 μm; after 500 thermal cycles, the flatness decreased by 1.4 μm to 1.7 μm, and the vacuum leakage rate was 6.8 × 10⁻⁶. -9 Up to 9.5×10 -9 Pa·m 3 / s, 2 to 4 new particles are added to the back side of the wafer. Comparative Example 1 uses existing technology, with a flatness of 5.2 μm before thermal cycling, and a flatness decrease of 7.6 μm after 500 thermal cycles, which is 543% of that in Example 1, and a vacuum leakage rate of 5.6 × 10⁻⁶. -7 Pa·m 3 / s is 68 times that of Example 1, and the combined defects of the three aspects lead to insufficient overall performance.

[0078] Comparative Example 2, without stepped vacuum aging, showed a flatness decrease of 9.2 μm after thermal cycling, which is 657% of that in Example 1, and a vacuum leakage rate of 4.8 × 10⁻⁶. -7 Pa·m 3 / s, the residual stress in the film layer is not released, which leads to the initiation and propagation of microcracks during thermal cycling. The microcracks penetrate the sealing layer, increasing the leakage rate, indicating that stepped vacuum aging has an important impact on the stability of the surface.

[0079] The first stage temperature of the comparative example 3 step vacuum aging was 120℃, which is lower than the critical range of 150℃-170℃ of this invention. After thermal cycling, the flatness decreased by 7.8μm. At 120℃, the microstructure relaxation driving force of the film layer was insufficient, and the residual stress was not fully released. The effect was close to that of no aging, indicating that the lower limit of the critical window of 150℃-170℃ has a critical effect.

[0080] The first stage temperature of the comparative example 4 step vacuum aging was 200℃, which is higher than the critical range of 150℃-170℃ of the present invention. After thermal cycling, the flatness decreased by 10.7μm, and the hardness of the oxide film was 398HV, which was 18% lower than 485HV in Example 1. At 200℃, the excessive reorganization of the microstructure of the film layer led to uneven dehydration and shrinkage, which caused microcracks at the film-substrate interface. The film layer density decreased and the hardness decreased, indicating that exceeding the upper limit of the critical window led to the performance degradation.

[0081] Comparative Example 5 did not undergo gas channel shielding treatment, and the oxide film inside the pores was not treated after oxidation, leaving the unintended oxide film on the pore walls. The vacuum leakage rate was 1.8 × 10⁻⁶. -7 Pa·m 3 / s is 22 times that of Example 1. Uneven oxide film thickness on the hole wall forms leakage channels. Residual electrolyte releases corrosive ions during service, accelerating hole wall corrosion. 15 new particles were added on the back side of the wafer, higher than the 3 in Example 1. This indicates that shielding treatment has a significant impact on hole wall smoothness and vacuum sealing. Even without milling to remove the oxide film, the unintended oxide film on the hole wall itself is a source of leakage and particulate matter.

[0082] Comparative Example 6 did not undergo air channel shielding treatment. After oxidation, the oxide film inside the hole was removed with a milling cutter, resulting in a vacuum leakage rate of 2.3 × 10⁻⁶. -7 Pa·m 3 / s is 28 times that of Example 1. The milling cutter leaves micro-scratches on the hole wall, which become leakage channels. The residual aluminum chips on the hole wall fall off during service and become a source of particulate matter. There are 22 new particles on the back of the wafer, which is higher than the 3 in Example 1. Compared with Comparative Example 5, it can be seen that the milling cutter removes the oxide film worse than the one that retains the oxide film. The secondary damage to the hole wall and the metal debris residue caused by the milling cutter are additional deterioration factors.

[0083] Comparative Example 7 used hot water sealing instead of fluorinated silane vacuum impregnation sealing, and the vacuum leakage rate was 8.5 × 10⁻⁶.-8 Pa·m 3 / s is 10 times that of Example 1. Hot water sealing only achieves surface sealing at the hydration expansion level, and the micropore depth direction filling rate is only about 60%. Fluorosilane vacuum impregnation achieves more than 90% depth filling under pressure difference drive and forms a fluorosiloxane cross-linked network after thermosetting. The sealing depth and durability are better than hot water sealing. After thermal cycling, the hot water sealing layer cracks due to the difference in thermal expansion coefficient with the oxide film, and the leakage rate further increases. This shows that the depth sealing effect of fluorosilane vacuum impregnation-thermosetting sealing is better than that of hot water sealing.

[0084] Comparative Example 8 used an atmospheric pressure air furnace instead of a vacuum furnace for aging. The aging temperature and holding time were the same as in Example 1. After thermal cycling, the flatness decreased by 7.4 μm, which was 529% of that in Example 1. Under atmospheric pressure, water vapor and oxygen in the air penetrated into the micropores of the oxide film at the aging temperature, hindering the orderly relaxation and recombination of the film's microstructure. The reaction of water vapor with alumina to generate boehmite caused uneven local volume expansion of the film, resulting in insufficient relaxation of the film's microstructure and microcracks caused by hydration expansion of the pore walls. This indicates that the vacuum environment plays an important role in achieving orderly structural relaxation and stress self-balancing of the film through step-age aging.

[0085] In summary, this invention achieves self-balancing of film stress through stepped vacuum aging at a critical window of 150℃-170℃, clean and oxide-free pore walls through polyvinyl alcohol shielding protection, and deep sealing through vacuum impregnation-thermal curing with fluorinated silane. These synergistic effects enable the aluminum wafer adsorption disk to possess both surface stability and vacuum sealing performance.

[0086] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.

Claims

1. A manufacturing process for an aluminum wafer adsorption disk of a wafer inspection device, characterized in that, Includes the following steps: Step 1: Select 6061-T6 aluminum alloy sheet and cut it into a circular blank; Step 2: Place the round blank in a vacuum heat treatment furnace, heat it to 250℃-270℃ at a rate of 2℃ / min-4℃ / min, hold it at that temperature for 8h-12h, and then cool it to room temperature at a rate of 1℃ / min-2℃ / min. Step 3: Perform CNC precision machining on the tempered blank, mill the outer circle to the designed diameter D, and machine the thickness to the designed thickness H minus 0.02mm-0.05mm. Mill air grooves on the front of the disc, and drill air channels vertically from the outer circumference of the disc to the center. Drill at least one non-penetrating guide hole vertically on the disc at each air groove position to make the guide hole connect with the air channel. Drill pin holes and positioning pin holes. Step 4: Coat the inner wall surfaces of the air groove, air passage, guide hole and pin hole with a soluble polyvinyl alcohol shielding layer. The soluble polyvinyl alcohol has a degree of polymerization of 1700-2000 and a degree of alcoholysis of 87%-90%. Coat with a polyvinyl alcohol aqueous solution with a mass concentration of 10%-15%. The shielding layer thickness is 0.1mm-0.3mm. After coating, dry at 60℃-80℃ for 1h-2h to cure the shielding layer. Step 5: The shielded billet is placed in a sulfuric acid-oxalic acid composite electrolyte for hard anodizing. The electrolyte temperature is -2℃ to 2℃, the sulfuric acid concentration is 180g / L-220g / L, the oxalic acid concentration is 8g / L-12g / L, and the initial current density is 0.8A / dm³. 2 -1.2A / dm 2 After oxidation for 15-20 minutes, the current density was gradually increased to 2.5 A / dm³. 2 -3.0A / dm 2 The total oxidation time is 90-120 minutes, forming a hard anodized film with a thickness of 40-60 μm on the surface of the blank. Step 6: Immerse the hard anodized blank in 50℃-60℃ deionized water for 20min-30min to dissolve and remove the shielding layer, and then rinse the air groove, air channel, guide hole and ejector pin hole inner wall with high pressure deionized water. Step 7: Place the cleaned billet in a vacuum heat treatment furnace, with a vacuum degree not exceeding 1×10⁻⁶. -2 Under Pa conditions, the temperature is increased to 150℃-170℃ at 1℃ / min-2℃ / min and held for 3h-5h, then increased to 190℃-210℃ at 0.5℃ / min-1℃ / min and held for 1h-2h, and then cooled to room temperature in the furnace. Step 8: Immerse the billet in a 2%-4% (w / w) 1H,1H,2H,2H-perfluorooctyltriethoxysilane ethanol solution, evacuate to 50Pa-200Pa and hold for 15-25 minutes, then slowly depressurize to atmospheric pressure and maintain for 10-15 minutes. Step 9: Heat the temperature to 120℃-140℃ at a rate of 2℃ / min-3℃ / min and hold for 1-2 hours for heat curing. Step 10: Precision grind the adsorption surface of the billet to the designed thickness H with a single feed rate of 1μm-3μm. After grinding, the oxide film on the adsorption surface should retain a thickness of not less than 30μm. Step 11: Ultrasonic cleaning, testing, and clean packaging.

2. The manufacturing process of the aluminum wafer adsorption disk for the wafer inspection equipment as described in claim 1, characterized in that, The thickness of the 6061-T6 aluminum alloy sheet mentioned in step one shall not be less than H plus 5mm, and the diameter shall not be less than D plus 10mm.

3. The manufacturing process of the aluminum wafer adsorption disk for the wafer inspection equipment as described in claim 1, characterized in that, The pressure of the high-pressure deionized water mentioned in step six is ​​0.5MPa-0.8MPa.

4. The manufacturing process of the aluminum wafer adsorption disk for the wafer inspection equipment as described in claim 1, characterized in that, In step seven, the temperature is increased at a rate of 1℃ / min-2℃ / min to 150℃-170℃, and the holding time is 4 hours.

5. The manufacturing process of the aluminum wafer adsorption disk for the wafer inspection equipment as described in claim 1, characterized in that, In step eight, evacuate to 100 Pa and hold for 20 minutes, then slowly depressurize to atmospheric pressure and hold for 12 minutes.

Citation Information

Patent Citations

  • Preparation method of anodic oxidation coating for semiconductor processing equipment component

    CN119121347A